2020
DOI: 10.32722/epi.v17i2.3458
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Youtube on English Vocabulary for Children 7-8 Years Old

Abstract: In the new norm era, children learn online from home. YouTube is used as a learning media to increase interest in learning English vocabulary. This qualitative descriptive study describes; how does YouTube affect the acquisition of English vocabulary and what is the impact of YouTube on the acquisition of English vocabulary. The study population was 7-8-year-old children. The research data is watching short English film and singing very simple English song from YouTube. The results of this study indicate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
0
5
0
2
Order By: Relevance
“…Children is supported by suitable material that can improve their vocabulary mastery, it is also proved by Devanti & Amalia (2018) that watching the video that was suitable with the theme could attract students' attention and the same time improve their vocabulary mastery. A similar study was also conducted by Mozes (2020) found that the activities related to vocabulary could send to learners' long-term memory as their knowledge.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Children is supported by suitable material that can improve their vocabulary mastery, it is also proved by Devanti & Amalia (2018) that watching the video that was suitable with the theme could attract students' attention and the same time improve their vocabulary mastery. A similar study was also conducted by Mozes (2020) found that the activities related to vocabulary could send to learners' long-term memory as their knowledge.…”
Section: Discussionmentioning
confidence: 61%
“…Applying Youtube Kids is as one way of using technology in teaching vocabulary in kindergarten. The fact today, modern learning media such as YouTube are currently influencing children curiosity and emotion because to operate it no needed basic and special knowledge, anytime and anywhere it can be open as long as the internet network is not in trouble (Mozes, 2020). YouTube Kids provides as a more controlled environment for children, making it easier and more enjoyable for them to explore on their own, and easier for parents and teacher to guide their journey as they discover new, exciting interests along the way.…”
Section: O1 X O2mentioning
confidence: 99%
“…YouTube merupakan situs web yang didirikan pada tahun 2005 (Herrero-, 2016;Parra, 2015). YouTube menyediakan video, musik, film pendek dan dokumenter, rekaman audio, trailer film, streaming langsung, dan dan video pendidikan (Mozes, 2020). Youtube merupakan media sosial yang populer dan mudah diakses oleh siapa saja (Amos, 2021;Bardakci, 2019;Keskin, 2018;W.…”
Section: Pendahuluanunclassified
“…Később pedig ezt a legfelsőbb bírói tekintélyt a mindenkori főpap és az abban a korban élő legnagyobb karizmatikus vezető mint főbíró 11 közös döntésére ruházták át. 12 Ez azt jelenti, hogy a társadalom 15 százaléka volt bíró: nem csak hogy tíz emberre jutott egyegy bíró, de ráadásul ötfokozatú fellebbviteli rendszer jött létre, ami a jogorvoslatot nagyon nagy mértékben biztosította, bár a fellebbvitel nem a mai értelemben értendő, mert maguk a bírák vitték feljebb az ügyeket, ha kétségesnek találták. 13 Diké A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport Folyóirata 106 A bírákat az első pillanattól fogva mindvégig hivatalosan kinevezték.…”
Section: A Tórai Bírósági Rendszerrőlunclassified